Cattle management system - Ravindren, Umaya Latha (2010)
Nowadays, the cattle farming are being a profitable sector in the growth of our nation.Therefore, many are getting involved in cattle farming business. Cattle Management System (CMS) is a system that fulfills the needs of a system for cattle farming. Cattle Management System (CMS) has functions such as edit cattle record, update the expanses of the cattle farm and update the immune table for the cattle. The prototype of CMS enables the users to manage the cattle farm. The methodology that will be used to develop CMS is Software Development Life Cycle that suits the web based system development. The scripting language for CMS is VB.Net , developed in Microsoft Visual Studio.Net 2008. The database for CMS was created by using Microsoft SQL Server 2005. This system is to be used by the administrator and staff, who is the farmer in the cattle farm.